Monitoring of Water Quality in Aquaculture Using IoT - Santhanakrishnan, C.; Reddy, C. Mukesh; Reddy, C. Mukesh; Revanth, S. Dinesh (International Journal of Psychosocial Rehabilitation, 2020)
Water is indeed a critical aspect of daily existence. Owing to the ecological crisis, water protection and recycling are essential to human life. In recent years, there has been a tremendous need for user-based development projects that could be quickly built through Internet of Things (IoT) technology. In this paper, we suggest a water monitoring device centered on IoT that monitors water levels and PH rates in real time. Our project is based on the principle that the water quality degree may be a very critical factor.This includes of a temperature sensor, a turbidity sensor, a pH sensor and a water level sensor which have been constantly tracked and a standard level is set. When the measurements go above the fixed value then the automated monitoring is carried out, i.e. the temperature is regulated by coolant engine, the filter motor is being used for turbidity, the water motor is used for the water pressure. Throughout this device, the detectors are linked to the IoT portal and are linked to the central server. The cloud server manages the information and the values should be reflected in the Smartphone application.